Wyzwania dla Kościoła w Polsce . Teologiczno-pastoralna refleksja w kontekście pandemii - Sawa, Przemysław (Studia Pastoralne, 2020)
Experience of the epidemic showed the strengths and weaknesses of Polish Catholicism. People’s longing for sacraments, liturgy and the mass during the restrictions related to the epidemic showed their attachment to the practice of faith. At the same time, the Church faced the need for fast technical development, especially in the area of the Internet (broadcasts, contact with the faithful). Simultaneously, various controversial issues are brought up regarding truths of faith, experiencing and understanding the life of the Church and understanding piety. There are three main challenges for the Church: proper formation of clergy and laity, shaping the right spirituality and opening to new forms of faith transmission and related pastoral conversion.